3,5-Bis(2-hexafluoro-isopropoxyl)phenyl: A Super-Fluorinated Moiety with Favorable Water-Solubility and Modifiability for 19F Magnetic Resonance Imaging - Yuhang Jiang; Jiahao Yang; Lexue Lin; Nan Xiong; Hongyu Lin; Jinhao Gao (Journal of the American Chemical Society, 2026)
Abstract Among molecular imaging techniques, 19F magnetic resonance imaging (19F MRI) is particularly attractive due to deep penetration and multiplexed molecular imaging. However, the further development of 19F MRI remains constrained by its limited sensitivity, which largely depends on fluorinated probe design and more fundamentally on the availability of high-performance fluorinated moieties that define probe signal intensity. Here we systematically establish 3,5-bis(2-hexafluoro-isopropoxy)phenyl (BHFIP) as a structurally simple yet highly capable fluorinated moiety for 19F MRI probe design. Starting from 1,3-bis(2-hexafluoro-isopropoxy)benzene, a simple two-step nitration-reduction procedure afforded 3,5-bis(2-hexafluoro-isopropoxy)aniline (BHFIP-NH2), a modifiable BHFIP-based building block. Besides its high fluorine loading of 12 chemically equivalent fluorine atoms, BHFIP was found to possess an intrinsically short 19F longitudinal relaxation time (T1), together enabling exceptionally high 19F MRI sensitivity. Its 19F chemical shift at approximately – 75 ppm is clearly distinguishable from those of established highly fluorinated moieties, supporting multiplexed 19F MRI. The two hydroxyl groups of BHFIP contribute to water solubility and enable O-modification, while BHFIP-NH2 further provides an additional amino handle for N-modification. Representative incorporation of BHFIP-NH2 into 19F MRI probes further verified that the advantages of BHFIP can be retained in functional probe molecules. This work establishes BHFIP as a promising fluorinated moiety for high-sensitive and multifunctional 19F MRI probes.